Perlindungan Hukum terhadap Desain Produk Industri Fashion di Indonesia - Nuryana; Juhriati; Nasrullah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This research aims to find out the legal regulations governing the protection of Fashion Industry Product designs in Indonesia and the obstacles faced in the implementation of legal protection of Fashion Industry Product Designs in Indonesia. This research uses a normative approach to examine legal protection of fashion industry product designs in Indonesia. The focus of this research is on the system of legal norms and the concept of justice based on public views on changes in the purpose of punishment in the Criminal Code (KUHP). The approach used includes conceptual, statutory, and comparative analysis to understand related legal concepts and principles. Secondary data sources used include legislation, literature, journals, and research results. Data collection was conducted through a literature study by analyzing written documents and related electronic sources. Thus, this research aims to understand the legal protection of fashion industry product designs in Indonesia and related concepts of justice. The results showed that the legal protection of fashion product designs in Indonesia is based on three pillars, namely the Industrial Design Law regulated in Law Number 31 of 2000 concerning Industrial Design, Copyright regulated in Law Number 28 of 2014 concerning Copyright, and Trademarks regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Although comprehensive, its implementation still faces challenges such as the complexity of registration and piracy. To optimize protection, regulatory harmonization, increased IPR awareness, and effective law enforcement are needed. Thus, Indonesia's fashion industry can develop sustainably and increase global competitiveness.